The surface area of a square pyramid can be calculated using the equation

$S=\frac {1}{2}lp+B$ Rearrange the surface area equation for the quantity of interest B
$B=$

1 answer

To rearrange the equation for the surface area \( S \) of a square pyramid, given by

\[ S = \frac{1}{2} lp + B, \]

we want to isolate \( B \).

To do this, we can start by subtracting \( \frac{1}{2} lp \) from both sides of the equation:

\[ S - \frac{1}{2} lp = B. \]

Thus, we have:

\[ B = S - \frac{1}{2} lp. \]

Therefore, the expression for \( B \) is:

\[ \boxed{B = S - \frac{1}{2} lp}. \]